IMPROVING SHIP REGISTER: TRADITIONAL REGISTRY VERSUS FLAG OF CONVENIENCE - SHAH, SYED KHAWAR ALI; IQBAL, KANWAR MUHAMMAD JAVED (The journal of contemporary issues in business and government, 2021)
The contemporary period of worldwide Shipping industry has observed fluctuating movements in ship registration procedures previously traditional and now to open registries, a substitute option for the business as usual practices. Afterwards the 20th century, the Flag of Conveniences (FOCs) have moulded a huge economic footmark worldwide with their increasing tonnage, hence influenced the traditional registry within the two processes. The shipping sector of Pakistan has not lived upon its full potential. The global share of Pakistani shipping market has shrunk during last three decades and there are several reasons including registration procedures of ships which is now a significant and major problem. Pakistan’s Ship registry procedure, though in compliance with international obligations, is an influential problem due to the close registry, and lengthy as well as burdensome process. The MSO 2001 ship’s registration rule, Merchant Marine Policy (MMP) of Pakistan 2001, and Ship Registration Rules 2002 govern the registry of ships. However, based on analysis, the current study argues that Pakistan requires revamping of its registry as well as legal/institutional/policy framework by reformulation and promulgation of fresh new version of MMP as the recent amendments have not curtailed the real issues so far outstanding vis-a-vis matter related to the ship registry procedure, in order to harness the real potential of shipping sector. It needs to formulate policies within the context of modern practices of FOCs as well as domestic registration, and at the same moment addressing the requirements to come across the responsibilities internationally.